National interest versus the common good: The Presidency in European Council agenda setting. (11th October 2012) - Alexandrova, Petya; Timmermans, Arco
Abstract The European Council is an institution which brings together the Heads of State, or Governments of the European Union (EU) Member States. For the Presidency, preparing the agenda of European Council meetings involves a tension between loyalties. Existing research is divided over the question whether the Presidency pushes its domestic policy agenda on the EU level. Using empirical data on the Conclusions of European Council meetings, and national executive speeches presented annually in five Member States, this article investigates the relationship between the policy agendas of the EU and its constituent countries. It tests whether national issue attention of the Presidency holder dominates the European Council agenda. The findings suggest that having the Presidency does not provide a de facto institutional advantage for agenda setting power for any of the countries in the sample. The analysis points out that normative and political constrains limit the leeway of presiding Member States to push for domestic agenda preferences in the European Council.